A practical smart metering using combination of power line communication (PLC) and WiFi protocols - Rafiei, M.; Eftekhari, S. M. (2012 Proceedings of 17th Conference on Electrical Power Distribution Networks, 2012)
Recently, smart metering has attracted much attention. Electricity distribution utilities are rapidly replacing traditional mechanical meters with so called smart meters. to provide a suitable smart metering system, variety of communication protocols have been proposed. Power-line communication (PLC) is a cost effective and secure communication protocol and does not require a separate communication line. In this paper a practical smart metering approach using combination of PLC and WiFi protocols is presented. The proposed approach can be used for both type of automatic meter reading (AMR) and advanced metering infrastructure (AMI).